Polish translations of Plato`s Dialogues from the Beginnings to the Mid-Twentieth Century - Mróz, Tomasz (1975- ) (Bruxelles: Éditions OUSIA)
The paper aims to present the main points in the history of Polish translations of Plato`s dialogues, which were closely bound up with Polish history and the revival of academic life in the interwar period. The focus is on translatory works by F.A. Kozłowski, A. Bronikowski, S. Lisiecki and W. Witwicki, who represented diverse approaches and applied different methods in rendering Plato`s texts into Polish.
Keywords: Plato (filozof; 427 p.n.e.-347 p.n.e.); Kozłowski, Felicjan Antoni (1805-1870); Bronikowski, Antoni (1817-1884); Lisiecki, Stanisław (1872-1960); Witwicki, W. (1878-1948); tłumaczenia